Superficial parotidectomy with or without great auricular nerve preservation. Is there a difference in postoperative sensory recovery rates and quality of life?. Issue 7 (September 2022) - Al-Aroomi, Maged Ali; Mashrah, Mubarak Ahmed; Zhou, Lu; Zhou, Wanhang; Du, Weidong; Sun, Changfu; Xie, Fuqiang
Abstract: The clinical implications of great auricular nerve (GAN) preservation or sacrifice during parotid surgery have long been a topic of controversy. This study aimed to compare sensory recovery rates and quality of life (QoL) in patients who had undergone superficial parotidectomy and had their GAN preserved or sacrificed. Fifty patients were prospectively analysed, 28 with the GAN preserved, and 22 with it sacrificed. The primary outcomes were tactile sensitivity and QoL. The secondary outcomes were operating times and other complications. There was a gradual improvement in tactile sensitivity in both groups, which showed a statistically significant difference favouring the preserved group at 1, 3, 6, and 9 months postoperatively (p<0.05). There was no statistically significant difference in tactile sensation for both groups at 12 months postoperatively. The overall sensory recovery rates in the GAN preserved and sacrificed groups after 1, 3, 6, 9 and 12 months were 42.8%, 42.8%, 57.1%, 57.1%, and 78.5%, and 0%, 0%, 13.6%, 27.3%, and 59.1%, respectively. According to the QoL assessment, there was a significant difference in mean (SD) loss of sensation scores (sacrificed group 0.86 (0.94) and preserved group 0.39 (0.62), p= 0.039). However, there were no statistical differences between the groups regarding other categories of the questionnaire. No significant difference was seen between groups regarding operating time and other complications. This study concluded that when evaluated objectively, sensory impairment ultimately lessened in severity in the second half of the first postoperative year. GAN preservation minimised sensation disturbance in long-term results, but overall QoL seemed to be unaffected following GAN preservation or sacrifice.